How loneliness impacts depression among Chinese college students throughout COVID-19: mediators of death anxiety and negative affect - Lv, Fangyan; Feng, Run; Tan, Jingbin; Li, Jie; Liu, Yanping; Gao, Dingguo (Frontiers in Psychiatry, 2025)
BackgroundThe COVID-19 pandemic, which is considered a public crisis, has profoundly affected the psychological well-being, behavioral patterns, and daily routines of individuals across the globe. Throughout the pandemic, the specter of death anxiety, triggered by the virus, has been an ever-present shadow, constantly haunting the minds of people and causing a significant impact on their mental health. Previous studies have indicated that the practice of home isolation during the pandemic led to a substantial rise in loneliness, especially among the student population, potentially precipitating depressive emotions during COVID-19. The present study aimed to investigate the influence of loneliness on depressive symptoms in Chinese college students during the COVID-19 pandemic with two mediators: death anxiety and negative affect.MethodsThis study employed a cross-sectional online design, collecting data from Chinese university students in March 2020. All participants (N=646; age M=19.960, SD=1.801; 49.690% males and 50.310% females) completed the UCLA Loneliness Scale, Self-rating Depression Scale, Templer Death Anxiety Scale in COVID-19 Context, and Negative Affect Scale. Multiple mediation analysis was utilized to analyze the data.ResultsThe results of this research revealed two vital findings. First, loneliness was positively correlated with death anxiety (r =.212, p <.001), negative affect (r =.317, p <.001), and depression (r=.545, p <.001). The chain mediation model showed that the risk factors of death anxiety and negative affect act as mediators in the link between loneliness and depression. This suggests that college students with higher levels of loneliness experienced increased death anxiety and negative affect, which subsequently increased depression.ConclusionOur research offers valuable insights into the link between loneliness and depression throughout COVID-19. The findings not only enrich the empirical literature on mental health in the context of pandemics—by revealing the serial mediating role of death anxiety and negative affect—but also provide practical implications for targeted mental health interventions.